Electrophysiology of Mind / Event-Related Brain Potentials and Cognition - Coles Michael G.H; Rugg Michael D (Oxford University Press, 1996)
This book shows how the event-related brain potential technique can contribute to topics central to cognitive psychology. Event-Related Brain Potentials: An Introduction, The ERP and Cognitive Psychology: Conceptual Issues, Mechanisms and Models of Selective Attention, Mental Chronometry and the Study of Human Information Processing, ERP Studies of Memory, Event-Related Potentials and Language Comprehension, Index.